Residents' attitude towards educational tourism in Malaysia - Abu Samah, Asnarulkhadi; Ahmadian, Maryam; Gill, Sarjit S.; Hendijani, Roozbeh Babolian (Canadian Center of Science and Education, 2013)
Educational tourism is known as an imperative sector in the tourism industry to expand its sustainability. Malaysia is increasingly recognized by students from around the world as the preferred choice for continuing education. Methods: This study used the data collected through a cross-sectional survey among residents in the Klang Valley, Malaysia. Interviewed questionnaires were used during the survey from December 2010 to January 2011. Results: The results showed that there is a significant difference in attitudes of local residents towards educational tourism. The finding also revealed that attention should be focused on the attitudes of residents with various job sectors. Conclusion: The difference between the residents' job is a critical issue in analyzing the impact of educational tourism and community development projects in Malaysia